Left ventricular noncompaction diagnosed following Graves′ disease - Habib Habib (Thieme Medical and Scientific Publishers Pvt. Ltd., 2016)
Isolated left ventricular noncompaction (LVNC) is a rare genetic cardiomyopathy. Clinical manifestations are variable; patients may present with heart failure symptoms, arrhythmias, and systemic thromboembolism. However, it can also be asymptomatic. When asymptomatic, LVNC can manifest later in life after the onset of another unrelated condition. We report a case of LVNC which was diagnosed following a hyperthyroid state secondary to Graves′ disease. The association of LVNC with other noncardiac abnormalities including neurological, hematological, and endocrine abnormalities including hypothyroidism has been described in isolated case reports before. To the best of our knowledge, this is the first reported case of LVNC diagnosed following exacerbation in contractile dysfunction triggered by Graves′ disease.